Pornografi dalatn Hukum Barat dan Hukum Islam^ (Kontribusi Konseptual bagi Pengaturan Pornografi dan Pornoaksi dalam Hukum Positif) - Agus Triyanta; Agus Triyanta (Fakultas Hukum Universitas Islam Indonesia, 2003)
In Islamic perspective, interpretation of pornography has correlation to the body. It means that it is something forbidden and it must be covered. It is certainly very quite different from the secular terminology, Islam denotes directly kinds or variation of forbidden deed in moral context or characters so that prohibition in Islam is fixed and clear. It has no correlation to the standard of society or the deed deals with the sexuality. The principle of sexual in Islam therefore could not change as easy as the perception of people on pornography.